FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN IUFD DI RSUD EMBUNG FATIMAH KOTA BATAM TAHUN 2018 - Hartalina, Hartalina; Sulistyawati, Tri Ribut (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Intra uterine Fetal Death (IUFD) refers to fetuses with no signs of life in utero, one of them due to asphyxia. In Indonesia, IUFD is making up to perinatal mortality rate of approximately 15 per 1000 live births. Reportedly, in Batam, the perinatal mortality rate was 4.7 per 1000 live births in 2017. According to the statistic released by Embung Fatimah General Hospital in 2018, the perinatal mortality rate related to IUFD is 26 per 317 live births. This research aims to discover the correlative factors on the prevalence of IUFD in Embung Fatimah General Hospital of Batam in 2018. The research design employs analytic survey with cross-sectional approach. The data collecting technique employs purposive sampling with total sample population of 76 women in labor. The univariate analysis is presented in the form of frequency distribution tables and the bivariate analysis applies chi-square with Î± <0.05. The bivariate findings reveal correlations between the age of the women and IUFD prevalence with Ï-value 0.003; between parity and IUFD prevalence with Ï-value 0.00; between pregnancy intervals and IUFD prevalence with Ï-value 0.015; and between hypertension and IUFD prevalence with Ï-value 0.01. In suggestion, healthcare workers and professionals are expected to advocate general public and especially women about the information about perinatal mortality including IUFD and the potential causality risks.